IMPLEMENTASI PEMBELAJARAN PAIKEM BERBASIS KEARIFAN LOKAL BUTON PO5 TERHADAP KARAKTER DAN KEMAMPUAN BERFIKIR KRITIS SISWA DALAM MEWUJUDKAN MERDEKA BELAJAR - Rosnawati, Veni; Ridzal, Dewi Asriani; Amri, Nurzil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research aims to determine the implementation of PAIKEM learning based on Buton PO5 local wisdom on students' character and critical thinking abilities in realizing independent learning. The type of research used was a Quasi Experiment with a Single Factor Independent Group Design which involved a research sample of 39 students selected at random. Research data was collected using test and non-test methods and analyzed using Anava A and Manova analysis. Based on the results of the Anova A analysis, the value of Fcount (32.852) ≥ Ftable (4.105) at a significance level of 5%, this shows that H1 is accepted. And the results of the Manova analysis show that the value of Fcount (38.960) with sig 0.001 < 0.05, which means that Ho is rejected and H1 accepted, this proves that there are simultaneous differences in the character and critical thinking abilities of students who take part in PAIKEM learning based on Buton PO5 local wisdom and students who take part in conventional learning.